2022
DOI: 10.3390/cancers14051247
|View full text |Cite
|
Sign up to set email alerts
|

Early Changes in Quantitative Ultrasound Imaging Parameters during Neoadjuvant Chemotherapy to Predict Recurrence in Patients with Locally Advanced Breast Cancer

Abstract: Background: This study was conducted to explore the use of quantitative ultrasound (QUS) in predicting recurrence for patients with locally advanced breast cancer (LABC) early during neoadjuvant chemotherapy (NAC). Methods: Eighty-three patients with LABC were scanned with 7 MHz ultrasound before starting NAC (week 0) and during treatment (week 4). Spectral parametric maps were generated corresponding to tumor volume. Twenty-four textural features (QUS-Tex1) were determined from parametric maps acquired using … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…KNN is a conceptually simple but powerful algorithm that is easy to use, interpret and implement [28]. It has been widely used in previous studies [29][30][31]. Furthermore, we found that XGBoost had the highest ACC in the training group.…”
Section: Discussionmentioning
confidence: 67%
“…KNN is a conceptually simple but powerful algorithm that is easy to use, interpret and implement [28]. It has been widely used in previous studies [29][30][31]. Furthermore, we found that XGBoost had the highest ACC in the training group.…”
Section: Discussionmentioning
confidence: 67%
“…ML and DL can also assist in post-radiotherapy management, such as distinguishing between the true and false progression of the tumor, radiation necrosis and tumor recurrence, and promoting clinical medical decision-making, thus improving PM ( 171 174 ). In addition, the image-based AI model can also assist radiologists in treatment evaluation, including predicting the response of individual cancer patients to chemotherapy or immunotherapy, and monitoring recurrence and metastasis ( 175 177 ). Several radiomics-based ML and DL models can predict patient prognosis, such as recrudesce-free and progression-free survival, survival rate, mortality, surgical results, postoperative metastasis and recurrence.…”
Section: Ai Assists Pm For Tumors Diagnosed Via Me...mentioning
confidence: 99%
“…Bhardwaj et al developed a classification model for predicting disease relapses in a cohort of 83 patients with LABC (28 recurrences and 55 non-recurrence) treated with NAC [ 60 ]. The pool of radiomics features included first-order statistical mean-value, GLCM-based textures, and GLCM-based higher-order textures from QUS spectral parametric images.…”
Section: Recurrence Predictionmentioning
confidence: 99%
“…The pool of radiomics features included first-order statistical mean-value, GLCM-based textures, and GLCM-based higher-order textures from QUS spectral parametric images. They reported the best model from baseline and changes in week 4 features, achieving 87% sensitivity, 75% specificity, 81% accuracy, and 0.83 AUC [ 60 ].…”
Section: Recurrence Predictionmentioning
confidence: 99%